DEVELOPING PROBLEM-BASED LEARNING MODEL BASED ON BAKIAK GAME FOR LEARNING MATHEMATICS AT ELEMENTARY SCHOOLS - Nur Imama; Sri Utaminingsih; Hilal Madjdi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
The purpose of this study was to develop a Problem Based Learning (PBL) model based on the traditional game “Bakiak” for learning mathematics at elementary schools. This study utilized Research and Development (R&D) methods with Borg and Gall model design which was simplified into 8 steps: (1) the potential and problems analysis; (2) data collection; (3) product design; (4) design validation; (5) design revision; (6) product testing; (7) product revision; and (8) trial use. The subjects in this study were fifth grade elementary school students at several schools in Kabupaten Pati. This study resulted in a PBL model based on “Bakiak” games for mathematics learning at elementary schools on the materials of speed, distance, and time for grade V. At the guiding phase, the investigation of individuals and groups was integrated with “Bakiak” games. The syntax for developing the model consisted of 7 stages, namely students’ orientation to problems, organizing students to learn, guiding individual and group investigations, assisting in data analysis, helping to find out mathematical concepts, developing work results, as well as analyzing and evaluating processes. The product and instruments were validated by media experts, material experts, and learning experts with a score of 3.47 (very good). Thus, the development of a PBL model based on “Bakiak” games was feasible to be used for learning mathematics.